Development of design thinking-based interactive digital media integrating kahoot! and heyzine flipbook to enhance students’ mathematical numeracy literacy through differentiated learning - Salma Millenia Utami; Aryo Andri Nugroho; Supandi (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Mathematical numeracy literacy remains a major challenge in senior high school mathematics learning, particularly in interpreting data, analyzing probability events, and solving contextual problems. This issue is exacerbated by the limited availability of interactive digital learning media that support differentiated instruction and diverse learning needs. Aims: This study aimed to develop and evaluate the feasibility of Design Thinking-based interactive digital media integrating Kahoot! and Heyzine Flipbook to enhance students’ mathematical numeracy literacy in probability learning. Method: This study employed a Research and Development (R&D) approach using the Design Thinking framework consisting of empathize, define, ideate, and prototype stages. The participants were 30 senior high school students selected through purposive sampling. Data were collected through observations, interviews, and validation questionnaires, then analyzed descriptively using qualitative and quantitative techniques. Results: The developed media successfully integrated gamified evaluation and interactive visual materials within differentiated learning environments. Validation results showed highly feasible categories, with scores of 90% from media experts and 92% from material experts. The media effectively supported probability learning, increased student engagement, and strengthened mathematical numeracy literacy. Conclusion: The developed interactive digital media have strong potential to support differentiated mathematics instruction and technology-enhanced numeracy learning in probability topics.